2022
DOI: 10.1021/acs.iecr.2c03417
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of β-Zeolite Nanocrystal Aggregates for the Alkylation of Benzene and Cyclohexene

Abstract: A dual-template strategy with poly(ethylene glycol) (PEG) and cetyltrimethylammonium bromide (CTAB) was employed to synthesize the β-zeolite nanocrystal aggregates with ultrafine and hierarchical structure (micropores combined with intra-mesopores and inter-mesopores), and the particle size of aggregates and the nanocrystal size of β-zeolites can be systematically tailored by tuning the molar ratios of CTAB/PEG. In the alkylation between benzene and cyclohexene, the β-zeolite nanocrystal aggregates synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…As reported in the literatures, , the band at ∼1545 cm –1 can be related to pyridine adsorption at Brønsted acid sites, and the band at ∼1455 cm –1 can be assigned to pyridine adsorption at Lewis acid sites. The band appearing at ∼1445 cm –1 can be attributed to pyridine H-bonded to OH groups on the surface of the material through the N atom. , Therefore, the adsorption peak at ∼1445 cm –1 should not be counted, and the Py-FTIR spectra were deconvoluted. The results are given in Table .…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…As reported in the literatures, , the band at ∼1545 cm –1 can be related to pyridine adsorption at Brønsted acid sites, and the band at ∼1455 cm –1 can be assigned to pyridine adsorption at Lewis acid sites. The band appearing at ∼1445 cm –1 can be attributed to pyridine H-bonded to OH groups on the surface of the material through the N atom. , Therefore, the adsorption peak at ∼1445 cm –1 should not be counted, and the Py-FTIR spectra were deconvoluted. The results are given in Table .…”
Section: Resultssupporting
confidence: 64%
“…The Brønsted and Lewis acid properties were identified by Py-FTIR, as shown in Figure 3b and Table 1. As reported in the literatures, 39,40 the band at ∼1545 cm −1 can be related to pyridine adsorption at Brønsted acid sites, and the band at ∼1455 cm −1 can be assigned to pyridine adsorption at Lewis acid sites. The band appearing at ∼1445 cm −1 can be attributed to pyridine H-bonded to OH groups on the surface of the material through the N atom.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…al. reported that hierarchical β-zeolite nanocrystal aggregates with intra-mesopores and inter-mesopores could be fabricated by using PEG 2000 and cetyltrimethylammonium bromide (CTAB) as dual templates in the presence of tetraethylammonium hydroxide (TEAOH) [54]. They found that the morphology and porosity of the resulting β-zeolites could be adjusted by tuning the amount of PEG 2000.…”
Section: Polyethylene Glycols (Pegs)mentioning
confidence: 99%